Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik dengan Pendekatan Metode Weighted Product di Kopi Wangsa - Sudrajat, Ridwan; Fajar, Indra Muchamad; Budi, Eko Setia (TIN: Terapan Informatika Nusantara, 2021)
The best and quality employees are company assets that will make the company grow rapidly. The selection of the best employees is a very important aspect of the company, it will affect the level of employee productivity so as to make employees who have productivity and produce company leaders who have good integrity. Based on the problems above, the authors design a Decision Support System (DSS) for selecting the best employees with the Weighted Product method for decision making based on the magnitude of the preference value which is calculated based on the variable value raised to the power of its weight. Where the rating must be raised first with the weight of the attribute concered, this process is the same as normalization. The existence of the Weighted Product method at Kopi Wangsa in order to get the best employees in accordance with the assessment made